Pengaruh Performance Exterior dan Tingkat Kegemukan Sebagai Penentu Harga Taksir Sapi Bali Jantan Di Kecamatan Awangpone Kabupaten Bone: The Effect of Exterior Performance and Fatness Level as Determinantsof the Estimated Price of Male Bali Cattle in Awangpone Subdistrict, Bone Regency - Ainun Aliyah; Muhammad Basir Paly; Rusny Rusny (Anoa: Journal of Animal Husbandry, 2023)
The selling price of beef cattle is usually influenced by the appearance of the cow. This is generally called "Exterior Performance". Exterior performance is considered as a determinant of the estimated price of cows as seen from hip height, chest circumference, body length and shoulder height of bb cows. This study aims to inform farmers and traders in determining the estimated price of male Balinese cattle based on the assessment of exterior performance and fatness level. This research was conducted in January 2023 in the Awangpone sub-district, Bone Regency. This study uses Multiple Linear Regression analysis tools with t and f tests. Data were obtained through surveys, direct interviews with farmers using questionnaires, and taking measurements and observations of male Balinese cattle. The results showed that hip height, chest circumference, body length, shoulder height, and fatness level together (simultaneously) had a significant effect on the selling price of male Balinese cattle in the Awangpone sub-district, Bone district and individually (partially) the variable hip height and shoulder height had no statistically significant effect on the selling price of male Balinese cattle. In contrast, chest circumference, body length, and fatness level significantly impacted the selling price of male Balinese cattle in the Awangpone sub-district, Bone district.